Deformation precursors of large earthquakes derived from long term GNSS observation data - Kaftan V.; Melnikov A. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2016)
The results of observation of Global Navigation Satellite Systems (GNSS) in areas of large earthquakes are analyzed in this article. The Earth''s surface deformation characteristics before, during and after the earthquake are researched, the results indicate the presence of abnormal deformation near their epicenters. The statistical evaluation of abnormal deformations with their root mean squares (rms) are presented. Conclusions about the possibilities of using local GNSS observation networks for evaluation of risk of strong seismic events are performed.
Keywords: EARTHQUAKE PRECURSORS; EARTH'S SURFACE DEFORMATION; GNSS OBSERVATION; SAN ANDREAS FAULT; LEAST SQUARE METHOD; SEISMIC CYCLE RELATED DEFORMATIONS; EARTHQUAKE INTERACTION; FORECASTING AND PREDICTION